2021
DOI: 10.1021/acs.est.1c01876
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen-Doped Carbon Dots Increased Light Conversion and Electron Supply to Improve the Corn Photosystem and Yield

Abstract: Fluorescent carbon dots (CDs) have been reported as an artificial antenna to amplify the harvesting ability of light and enhance photosynthesis in plants. However, the main mechanism of this promotive effect and contributions of CDs’ structure are unclear. Herein, CDs and nitrogen (N)-doped CDs (N-CDs) with blue fluorescence were synthesized, and they could promote photosynthesis and growth of corn at an application concentration of 50 mg·L–1 or lower, compared to the control. Foliar application of N-CDs (5 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
88
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(91 citation statements)
references
References 56 publications
3
88
0
Order By: Relevance
“…In these studies, the investigators studied the impacts of CDs on photosynthesis mainly by directly applying CDs to chloroplasts, [7][8][9] seed priming 10 or foliar spraying. 11,13 However, little information is available on whether root applied CDs can enhance photosynthesis in leaves after translocating from plant roots to leaves through vascular system. Recent studies mainly focused on the roles of CDs in promoting growth of plants.…”
Section: Introductionmentioning
confidence: 99%
“…In these studies, the investigators studied the impacts of CDs on photosynthesis mainly by directly applying CDs to chloroplasts, [7][8][9] seed priming 10 or foliar spraying. 11,13 However, little information is available on whether root applied CDs can enhance photosynthesis in leaves after translocating from plant roots to leaves through vascular system. Recent studies mainly focused on the roles of CDs in promoting growth of plants.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study has shown that N-doping blue-emitting CDs could increase maize yield by 24.5%. 40 Further studies have shown that N-doping can increase the electron density and forbidden bandwidth of CDs compared to undoped CDs, and reduce the recombination efficiency of electron hole pairs, thus providing electrons to the photosystem as electron donors. The net photosynthetic rate was increased by accelerating electron mobility.…”
Section: Artificial Light-harvesting Antennae and The Mechanismmentioning
confidence: 99%
“…Published studies on precursors, synthesis methods, quantum yields, absorption and emission wavelengths, crop species, and mechanisms of CDs are summarized in Table 1. 32,34,[39][40][41][42][43][44][45][46] Next, we will discuss the influence of PL color of CDs on photosynthesis.…”
Section: Artificial Light-harvesting Antennae and The Mechanismmentioning
confidence: 99%
See 2 more Smart Citations